Emirati women's experience of job satisfaction: Comparative effects of intrinsic and extrinsic factors - Seydahmet Ercan (South African Journal of Business Management, 2018)
Living and working in a patriarchal culture that encourages modesty, female Emirati employees might face unique challenges such as a male-dominated work environment, higher emotional labour and lack of role models to follow. These challenges potentially shape Emirati women's job-related attitudes and values in a way distinct from that of Western women. Thus, rather than relying on the results of studies conducted in Western countries, researchers should collect data from Emirati women to gain a more accurate understanding of their job attitudes. Consequently, this study examines the effects of some intrinsic and extrinsic factors on Emirati women's job satisfaction. The factors include pay, promotion opportunities, job security, job difficulty, job content quality and interpersonal relations. The results of a hierarchical regression analysis based on data obtained from 364 female Emirati employees indicate that pay and promotion opportunities do not have significant effects, whereas job security, job content quality and interpersonal relations have significant positive effects, and job difficulty has a significant negative effect on Emirati women's job satisfaction. The results further indicate that intrinsic factors explained 10% of variance in job satisfaction above and beyond the extrinsic factors and promotion opportunities. The article discussed the possible meaning of these findings in the context of working in a male-dominated work environment and living in a culture that encourages and values modesty.
Keywords: 650